Review on bonding techniques of CFRP in strengthening concrete structures - Jumaat, Mohd Zamin; Rahman, M.M.; Rahman, M.A. (International Journal of Physical Sciences, 2011)
Selecting appropriate bonding technique is crucial for strengthening and repairing concrete structures as different bonding techniques have different performances. A state-of-the-art review of different bonding techniques that is epoxy bonding technique, prestressed strengthening technique, unbonded anchored technique/mechanically fastened technique using CFRP is dealt and the corresponding advantages and disadvantages are highlighted in this review. Existing unbonded anchored techniques/mechanically fastened techniques are critically reviewed and compared to the other conventional strengthening techniques which will help in selecting the appropriate bonding technique for strengthening and repairing concrete structures. Future recommendations in this field are also indicated in this paper.